Jatropha curcasand Ricinus communisdisplay contrasting photosynthetic mechanisms in response to environmental conditions (Scientia Agricola, 2015)
Higher plants display different adaptive strategies in photosynthesis to cope with abiotic stress. In this study, photosynthetic mechanisms and water relationships displayed byJatropha curcasL. (physic nuts) andRicinus communisL. (castor bean), in response to variations in environmental conditions, were assessed.R. communis showed higher CO2 assimilation, stomatal and mesophyll conductance thanJ. curcas as light intensity and intercellular CO2 pressure increased. On the other hand,R. communis was less effective in stomatal control in response to adverse environmental factors such as high temperature, water deficit and vapor pressure deficit, indicating lower water use efficiency. Conversely,J. curcas exhibited higher photosynthetic efficiency (gas exchange and photochemistry) and water use efficiency under these adverse environmental conditions.R. communisdisplayed higher potential photosynthesis, but exhibited a lowerin vivo Rubisco carboxylation rate (Vcmax) and maximum electron transport rate (Jmax). During the course of a typical day, in a semiarid environment, with high irradiation, high temperature and high vapor pressure deficit, but exposed to well-watered conditions, the two studied species presented similar photosynthesis. Losing potential photosynthesis, but maintaining favorable water status and increasing non-photochemical quenching to avoid photoinhibition, are important acclimation mechanisms developed byJ. curcas to cope with dry and hot conditions. We suggest thatJ. curcas is more tolerant to hot and dry environments thanR. communis but the latter species displays higher photosynthetic efficiency under well-watered and non-stressful conditions.